Risk Factors of Prolonged Mechanical Ventilation in Infants With Pierre Robin Sequence After Mandibular Distraction Osteogenesis: A Retrospective Cohort Study - Zhang, Na; Mao, Zhe; Cui, Yingqiu; Xu, Yingyi; Tan, Yonghong (Frontiers in Pediatrics, 2021)
Background: After mandibular distraction osteogenesis (MDO), most infants with Pierre Robin sequence (PRS) require mechanical ventilation to assist their breathing. However, the optimal duration of intubation during early mandibular distraction osteogenesis activation is poorly understood. This retrospective study was carried out to identify perioperative risk factors of prolonged mechanical ventilation in infants undergoing MDO. Methods: A total of 95 infants with PRS underwent MDO at Guangzhou Women and Children’s Medical Center between 2016 and 2018, and the clinical records of 74 infants who met the selection criteria were analyzed. Of the 74 infants, 26 (35.1%) underwent prolonged mechanical ventilation, 48 (64.9%) did not. t-test, Wilcoxon Sum Rank test or chi-squared test were performed to compare variables that might associate with prolonged mechanical ventilation between the two groups, and then, significant variables identified were included in the multivariate logistic regression model to identify independent variables. Results: Univariate logistic regression analysis revealed that age, preoperative gonial angle, and postoperative pulmonary infection were associated with prolonged mechanical ventilation (all P < 0.05). Multivariate logistic regression analysis confirmed that the preoperative gonial angle and postoperative pulmonary infection were independent risk factors of prolonged mechanical ventilation (both P < 0.05). Conclusions: Infants with PRS and smaller preoperative gonial angle or postoperative pulmonary infection may be more likely to undergo prolonged mechanical ventilation after MDO. For others, extubation may be attempted within 6 days after MDO.